Say my name! An empirical study on the pronounceability of identifier names - Gresta, Remo; Cirilo, Elder (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2021: Anais do IX Workshop de Visualização, Evolução e Manutenção de Software, 2021)
Identifiers represent approximately 2/3 of the elements in source code, and their names directly impact code comprehension. Indeed, intention-revealing names make code easier to understand, especially in code review sessions, where developers examine each other's code for mistakes. However, we argue that names should be understandable and pronounceable to enable developers to review and discuss code effectively. Therefore, we carried out an empirical study based on 40 open-source projects to explore the naming practices of developers concerning word complexity and pronounceability. We applied the Word Complexity Measure (WCM) to discover complex names; and analyzed the phonetic similarity among names and hard-to-pronounce English words. As a result, we observed that most of the analyzed names are somewhat composed of hard-to-pronounce words. The overall word complexity score of the projects also tends to be significant. Finally, the results show that the code location impacts the word complexity: names in small scopes tend to be simpler than names declared in large scopes.